2015
DOI: 10.1021/acs.jctc.5b00457
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Size-Consistency of Orbitally Noninvariant Size-Extensive Multireference Perturbation Theories: A Case Study Using UGA-SSMRPT2 as a Prototype

Abstract: Profiling a potential energy surface (PES), all the way to dissociate a molecular state into particular fragments and to display real or avoided crossings, requires a multireference description and the maintenance of size-consistency. The many body methods, which suit this purpose, should thus be size-extensive. Size-extensive theories, which are invariant with respect to transformation among active orbitals are, in principle, size-consistent. Relatively cheaper size-extensive theories, which do not possess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 121 publications
0
16
0
Order By: Relevance
“…Due to the explicit connective nature of the working equation(s), the parent SSMRPT method [12] furnishes size-consistent description of any system composed of noninteracting fragments, provided that the reference space adopts a direct product form. [15,31] Note that SSMRPT does not conserve orbital invariance of the underlying CAS wavefunction. If the CAS reference function fails to satisfy the separability property, the reference energy itself is not sizeconsistent which is not corrected by the addition of electron correlation (except full CI).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the explicit connective nature of the working equation(s), the parent SSMRPT method [12] furnishes size-consistent description of any system composed of noninteracting fragments, provided that the reference space adopts a direct product form. [15,31] Note that SSMRPT does not conserve orbital invariance of the underlying CAS wavefunction. If the CAS reference function fails to satisfy the separability property, the reference energy itself is not sizeconsistent which is not corrected by the addition of electron correlation (except full CI).…”
Section: Introductionmentioning
confidence: 99%
“…Designing methods which can accurately treat MR‐systems at an affordable computational price present a challenge to the practitioners of electronic structure theory . Various workers in the realm of electronic structure theory have suggested different approaches to address these problems . Reviews of various MRPT methods can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensivity is always an issue to consider, especially for a CC theory. While the expressions reported above appear connected at first glance, spin cumulants represent a non trivial problem [44,45] and for this reason the analysis is put off to further study.…”
Section: Resultsmentioning
confidence: 99%